2010
DOI: 10.1021/nl9035302
|View full text |Cite
|
Sign up to set email alerts
|

Conductance Anisotropy in Epitaxial Graphene Sheets Generated by Substrate Interactions

Abstract: We present the first microscopic transport study of epitaxial graphene on SiC using an ultrahigh vacuum four-probe scanning tunneling microscope. Anisotropic conductivity is observed that is caused by the interaction between the graphene and the underlying substrate. These results can be explained by a model where charge buildup at the step edges leads to local scattering of charge carriers. This highlights the importance of considering substrate effects in proposed devices that utilize nanoscale patterning of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
95
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(104 citation statements)
references
References 34 publications
9
95
0
Order By: Relevance
“…This suggests that transport properties in graphene bilayers grown on epitaxial SiC inherit the non-uniformity observed in AFM and Raman measurements of graphene bilayers. Furthermore, the bilayer sample exhibits regions of high mobility (>2000 cm 2 /Vs) and low carrier density (<0.9x10 13 investigations showing a correlation between macroscopic electrical measurements and surface morphology [38][39][40]. If these properties could be uniformly achieved over large areas, then bilayers grown on epitaxial SiC layers could offer a substantial improvement to the current technique of graphene grown directly on SI SiC substrates in the context of a device oriented application.…”
Section: Discussionmentioning
confidence: 98%
“…This suggests that transport properties in graphene bilayers grown on epitaxial SiC inherit the non-uniformity observed in AFM and Raman measurements of graphene bilayers. Furthermore, the bilayer sample exhibits regions of high mobility (>2000 cm 2 /Vs) and low carrier density (<0.9x10 13 investigations showing a correlation between macroscopic electrical measurements and surface morphology [38][39][40]. If these properties could be uniformly achieved over large areas, then bilayers grown on epitaxial SiC layers could offer a substantial improvement to the current technique of graphene grown directly on SI SiC substrates in the context of a device oriented application.…”
Section: Discussionmentioning
confidence: 98%
“…Yet, the overestimated step edge resistance of the winding terraces may suggest that graphene's resistance is further augmented by local morphology. Such contribution could be a consequence of residual Si atoms aggregated in the step edge area 55 or growth disorder near the step edges leading to deterioration of graphene's quality and promoting short-range scattering. 72 …”
Section: -5mentioning
confidence: 99%
“…In Ref. 55 (2014) suggested that the conduction anisotropy is a reflection of both geometric anisotropy and the extent of residual silicon atoms aggregated at the step edges, where they enhance carrier scattering.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the graphene sheet resistance was highly dependent upon the orientation of the TFM pattern. Conductance anisotropy in graphene sheets on semi-insulating SiC has been studied using scanning tunneling microscopy, and this observation is a verification of this effect on a much larger scale [8]. The average contact resistance was 1.50-mm, independent of orientation.…”
Section: Characterization and Analysismentioning
confidence: 83%